Penerapan Metode Pembelajaran VBL (Video Based Learning) Dalam meningkatkan Hasil Belajar Peserta Didik Pada Cerita Fabel “Kecerdikan Menumbuhkan Kebaikan” Tema 7 Kebersamaan Subtema I - Anggi Solihah; Budiana; Ahmad Hidayat (Universitas Garut, 2025)
This study aims to improve students’ learning outcomes in Indonesian language learning, particularly on the fable story entitled “Kecerdikan Menumbuhkan Kebaikan”, through the implementation of the Video Based Learning (VBL) method. This research employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which was conducted in two cycles. The research subjects were 20 second-grade students of MI Darul Huda Sadahiang. Data were collected through learning outcome tests, observations, and interviews. The results of the study indicate that the application of the Video Based Learning method can improve students’ learning outcomes. The average score in the pre-cycle was 65%, increased to 68.5% in Cycle I, and further increased to 75.5% in Cycle II. Based on these findings, it can be concluded that the Video Based Learning method is effective in improving students’ learning outcomes in Indonesian language learning on fable story material at Madrasah Ibtidaiyah. Keywords: Video Based Learning, Learning Outcomes, Fable Story, Indonesian Language